COVID-19: epidemiology, pathogenesis and immununological basis - Nguepou Tchopba, Christèle; Ataba, Essoham; Katawa, Gnatoulma; Gambogou, Banfitebiyi; Ritter, Manuel; D. Karou, Simplice; Ameyapoh, Yaovi (Al-Nahrain Journal of Science, 2020)
Background: World Health Organisation (WHO) declared COVID-19 as a Public Health Emergency of International Concern (PHEIC). This review presents the geographical distribution of COVID-19 as of 31st May 2020, the virus pathogenesis, the evolution of total confirmed cases and global death toll of COVID-19 from 31st December 2019 to 31st May 2020 on the 5 continents and to display the immunological basis of the disease.Methods: Literatures were found by searching online databases. The evolution of total confirmed cases and total confirmed deaths, every two weeks, were plotted using GraphPad Prism 5.1 software.  Results: As of 31st May 2020 at 10:00 am, WHO reported 218 countries and territories concerned by COVID-19 on the 5 continents, with 5934936 total confirmed cases and 367166 total deaths. SARS-CoV-2 has a spherical shape with some pleomorphism. The infection pathogenesis significantly depends on the binding between spike protein and its receptor (ACE2 principally). Clinical manifestations of the disease vary according to host immunity and range from mild to fulminant.. The main mechanism for acute respiratory distress syndrome (ARDS) is the “cytokine storm”.  The virus employs many strategies to evade the immune response.Conclusion: COVID-19 has wreaked a lot of havoc. Investigations are still ongoing for the development of treatment and vaccines. In the meantime, measures are being taken to prevent and limit contacts.Keywords: COVID-19, epidemiology, pathogenesis, immunological response